(untitled) (Texas Journal of Medical Science, 2024)
The effectiveness of a comprehensive treatment and rehabilitation approach for post-burn and mechanical injuries to the upper extremities has been confirmed through the analysis of both immediate and long-term outcomes. The strategy, involving scar correction surgeries, autodermotransplantation, and physiotherapy, has yielded successful and sustainable results. Patients facing scar contractures and trophic impairments have regained mobility and improved their quality of life, underscoring the efficacy of our treatment approach